Hydrogen Passivation of M–N–C (M = Fe, Co) Catalysts for Storage Stability and ORR Activity Improvements. Issue 38 (8th August 2021) - Liu, Jieyuan; Wan, Xin; Liu, Shiyuan; Liu, Xiaofang; Zheng, Lirong; Yu, Ronghai; Shui, Jianglan
Abstract: M–N–C (M = Fe, Co) are highly active nonprecious metal electrocatalysts for the oxygen reduction reaction (ORR) and other applications. Although their operation stability has been extensively studied in proton‐exchange‐membrane fuel cells, the storage stability that determines the performance maintenance before use has not yet been understood. Here, it is found that long‐term exposure of M–N–C catalysts in air would cause surface oxidation and hydroxylation, resulting in significant decrease of ORR activity and fuel‐cell performances. Hydrogen passivation is demonstrated to be an effective strategy to protect the atomic M–N4 active sites and improve the storage stability of the catalysts. In addition, the hydrogen‐termination can also reduce the ORR energy barrier and increase the utilization of active sites, leading to the improvements of fuel‐cell activity and power density. Notably, these findings help to understand the storage‐associated degradation and protection of M–N–C catalysts. Abstract : The storage stability of M–N–C catalysts is investigated. Surface oxidation and hydroxylation are found to be responsible for serious performance degradation after long‐term storage in ambient environment. A hydrogen passivation strategy is proposed to modify and protect the catalytic active sites, which can greatly improve the storage stability as well as the fuel‐cell activity and power density of the catalysts.